Analysis of the Spread of Gripep and the Control of Its Symptoms in Indonesian Society - Kusumawati, Prima Dewi; Kurniati, Ana; Putri, Elvina Triana; Amri, Choirul; Koesnadi, Koesnadi (International Journal of Public Health Excellence (IJPHE), 2025)
This study investigates the emergence and impact of "Gripep," a term used in Indonesia to describe a combination of flu-like symptoms and psychosocial distress. Utilizing qualitative analysis, we explore the socio-cultural factors contributing to the spread of "Gripep" within Indonesian society. The research highlights the increasing prevalence of these symptoms, which manifest as heightened anxiety, depressive tendencies, and general unease. Through a comprehensive review of recent academic literature, expert interviews, and public health reports, we identify key influences such as urbanization, cultural practices, and mental health stigma that exacerbate the condition. The findings reveal significant challenges in healthcare management, underscoring the need for integrated care that addresses both physical and mental health aspects. Furthermore, the study evaluates current public health strategies aimed at controlling "Gripep," emphasizing the importance of culturally sensitive interventions. The results indicate that without timely detection and effective management, "Gripep" may lead to long-term health consequences, impacting individuals and communities. This research aims to inform policymakers and healthcare professionals, providing insights for the development of evidence-based interventions to combat this emerging public health challenge in Indonesia.